Cost‑effectiveness Analysis of Financial Support Instruments for Small and Medium‑sized Enterprises in the European Union - Maciej Woźniak (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the article is to evaluate the level and diversification of the cost‑effectiveness of selected financial support instruments4 for small and medium‑sized enterprises (SMEs) in the European Union (EU). Based on a literature review, 2 cognitive gaps were identified and 4 research questions were formulated. The realisation of the objective required the conducting of empirical analyses on a sample of 6,495 SMEs from 6 countries of the EU which were beneficiaries of 9 financial instruments. The obtained results indicate that the schemes under study show high variability of cost‑effectiveness that depends on the type and configuration of support instruments, their scope of impact and the level of economic development of the EU countries.